Hubungan Kualifikasi Pendidikan Guru terhadap Kompetensi Mengajar dan Hasil Mengajar - Nurlaela Nurlaela; Syamsul Aripin (Al-Munawwarah : Jurnal Pendidikan Islam, 2025)
This study aims to examine the relationship between teachers' educational qualifications, teaching competence, and student learning outcomes through a library reseach approach. Educational qualifications are considered one of the key factors influencing teacher’s ability to design, implement, and evaluate learning effectively. By reviewing various literature sources, scientific journals, and previous research findings, this study finds a consistent relationship between the level of teachers’educational qualifications and their teaching competence, as will as its impact on student learning outcomes. These findings highlight the importance of improving teacher academic qualifications as part of a strategy to enhance overall education quality